Palliative care patients' perceptions of the work involved in understanding and managing the network of care provision surrounding them - Jarrett, Nikki; Porter, K.; Davis, C.; Lathlean, J.; Duke, S.; Corner, Jessica; Addington-Hall, J. (BMJ Publishing Group, 2015)
Objective: To explore the work carried out for cancer palliative care patients in understanding and dealing with the often large network of care provision surrounding them.